2022
DOI: 10.3390/ijerph191610451
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effects of Different Exercise Modes on Inflammatory Response in the Elderly

Abstract: The aim of this study was to investigate the effects of different exercise modes on improving inflammatory response in the elderly. For the research methodology, databases such as CNKI (China National Knowledge Infrastructure), Wanfang Data, Pubmed, Web of Science, and EBSCO were selected for searching. The Cochrane Risk of Bias (ROB) tool was used to evaluate the methodological quality of the included studies, and RevMan5.4.1 analysis software was applied for the statistical analysis. A total of 31 studies (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Aside from significantly lower LPS-induced CCL-2 release in whole-blood cultures, we observed no further significant changes in inflammatory markers on protein or gene expression levels in our control group, receiving only exercise. This is unexpected, since it has been reported that exercise in general is improving the inflammatory response in old adults [ 7 ]. However, our results are in line with another study, which observed no changes in IL-6, IL-10, IL-1β, and TNF-α on protein and gene expression levels after nine weeks of vibration training (3 days/week) in community-dwelling old adults [ 18 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Aside from significantly lower LPS-induced CCL-2 release in whole-blood cultures, we observed no further significant changes in inflammatory markers on protein or gene expression levels in our control group, receiving only exercise. This is unexpected, since it has been reported that exercise in general is improving the inflammatory response in old adults [ 7 ]. However, our results are in line with another study, which observed no changes in IL-6, IL-10, IL-1β, and TNF-α on protein and gene expression levels after nine weeks of vibration training (3 days/week) in community-dwelling old adults [ 18 ].…”
Section: Discussionmentioning
confidence: 97%
“…The term “inflamm-aging” has recently been extended to “inflamm-inactivity”, since it is recognized that a sedentary lifestyle causes a relevant proportion of inflammatory processes [ 5 ], which are reversible with regular exercise even in higher age, as different meta-analyses have shown [ 6 , 7 ]. Furthermore, a lower dietary inflammatory burden has been associated with lower systemic inflammation in old adults [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a link between cardioprotection induced by exercise and decreased endothelial activation remains to be established. Exercise has been shown to increase the bioavailability of NO, specifically eNO and IL-6, both of which play an anti-inflammatory role [ 105 , 106 , 107 ]. It is important to note that excessive, prolonged, and strenuous overtraining can lead to damaging oxidative stress, with an attendant decrease in NO bioavailability.…”
Section: Exercisementioning
confidence: 99%
“…Calisthenics causes improvements in balance, muscle strength, mobility, cognition, sleep disorders, aerobic capacity, and emotional problems (9,(11)(12)(13). While the effects of different kinds of exercises on depression, fatigue, and sleep disorders in elders have been widely discussed (1,(14)(15)(16), it has been recorded that calisthenic exercises for elders are not as focused on young adults.…”
Section: Introductionmentioning
confidence: 99%